The Impacts of Ultra-Slim Plus and Slim Smart on the Morphology of Kidneys and Renal Function of Albino Rats as Weight Reducing Drugs - Abdul Sadiq, Hasan Akbar Khan, Muhammad Naveed Najeeb, Ali Ahmed, Arisha Sana Memon, Naveed Shuja (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and objectives: Current study was designed to investigate the effects of two weight reducing drugs i.e. Slim Smart and Ultra-Slim Plus on kidneys and renal function. Experimental Study: This study was conducted in the Experimental Institute (Animal House) of The University of Lahore, Anatomy departments and Biochemistry department from November 2021 to May 2022. A total 25 adult male albino rat were collected and divided them into three different groups. Plain distilled water, Slim Smart and Ultra Slim plus were used in glass bottles. Under an anatomical microscope, the TA index was used to quantify interstitial fibrosis, glomerular hyalinization, vascular alterations, and tubular atrophy. Cell infiltration was computed as a percentage of inflammatory cells / HPF, and the cortical medulla ratio (C / M) was also calculated. SPSS version 20 was used to gather and analyze the raw data. One-way ANOVA was used to compare groups for quantitative variables such as renal cell infiltration. Group (mean ± standard) error was used for this analysis. Post-tacky tests were also used for cortical medullary ratios and (p< 0.05) was considered important. Results: Sections of Albino Rate kidney stained with H&E and PAS and examined histologically revealed mesangial cellular hypertrophy, thickened vascular walls, and lymphocyte infiltration. The results of group-A and group-C were significant but in group-B much inflammation was seen. A slightly significant changes (p< 0.05) were seen in serum creatinine and blood urea levels in different groups. Conclusion: Slim Smart and Ultra Slim Plus induce mesangial hyper cellularity and lymphocyte infiltration, as well as thickening of blood vessel walls. These alterations are consistent with interstitial nephritis, thus individuals with renal problems should use these medications with care.